The Impact of The Effectiveness of Performance Evaluation on Improving Organizational Performance From Perspective of The Balanced Scorecard: The Case of The Ministry of Justice in Jordan - Al-Qarala, Alaa Abdul Hafez Al - Zghailat (Journal of Economic, Administrative and Legal Sciences, 2018)
The present study aims at identifying the impact of effectiveness of performance evaluation on improving organizational performance through the non-financial dimensions of balanced scorecard as Learning and growth, service recipients, and internal process in the Ministry of Justice. The study population included all staff in the Ministry of Justice, the study carried out on a random sample of (506), The information was collected by a questionnaire distributed to the sample. The study depended on (442) questionnaires were returned for valid statistical analysis. The most important results of the study were that: There is a statistically significant positive impact of performance evaluation on organizational performance in its three dimensions (learning and growth, service recipients, internal process) in the Ministry of Justice; The existence of statistically significant differences in the respondents’ perceptions of the effectiveness of the performance evaluation due to the variables of the academic qualification, age, functional experience, gender, job level. The study recommended the following: The evaluation system should be based on interviews, where staff are informed of the results of their performance evaluation to provide access and improve supervision methods; to establish a committee directly related to senior management to be responsible for following up and reading the results of evaluation and following up the recommendations, and using them in decision-making and improving career path.